Monotonicity of the period of a non linear oscillator. (July 2016) - Benguria, Rafael D.; Cristina Depassier, M.; Loss, Michael
Abstract: We revisit the problem of monotonicity of the period function for the differential equation u ″ − u + u p = 0 and give a simple proof of recent results of Miyamoto and Yagasaki.